HUBUNGAN DURASI PENGGUNAAN SMARTPHONE DENGANNYERI LEHER PADA MAHASISWA UPN VETERAN JAKARTA - Bayu Rizki Sidik Fathonah (2021)
Smartphones are considered to be the most popular portable electronic devices today. The number of smartphone users worldwide is estimated to reach 3.5 billion by the end of 2019 and is expected to reach 3.8 billion by 2021. Some literature states that the current use of mobile phones has overcome musculoskeletal complaints (MSK), and the most common symptoms of MSK. is pain. One of the pains that can arise from long-term cell phone use is neck pain. The purpose of this study was to determine the duration of smartphone use with neck pain in UPN Veterans Jakarta students. The design of this study was a cross sectional study through a questionnaire. The parameters used to measure the duration of smartphone use are hours and use NRS (Numeric Rating Scale). Based on SPSS 25 data, the Pearson Corelation NRS correlation coefficient with p value = 1 and the duration of smartphone use with p value = 0.388. The conclusion is that the duration of smartphone use with neck pain has a weak relationship with the level of the relationship.